Anthropogenic activity and the destruction of coral reefs in the waters of small islands. Issue 1 (October 2020) - Fudjaja, L; Viantika, N M; Rani, C; Nurdin, N; Priosambodo, D; Tenriawaru, A N
Abstract: Coral reefs have a very important function in maintaining the balance of marine ecosystems, but the pressure of anthropogenic activity can damage the coral reef ecosystem. This research aims to analyses the activities and behaviors of communities that cause damage to the coral reefs of the small island Island waters of the Spermonde Islands. This study was conducted on 8 small islands of the Spermonde Islands using a qualitative descriptive approach. The results showed that anthropogenic activity conducted by the small islands, tends not to be environmentally friendly. As a result there is damage and reduced living coral reefs are quite large. It's been identified there are 13 island community activities that could damage the coral reef ecosystem. In order to support the sustainability and existence of coral reefs, it is a must that every stakeholders for having collaboration in the management of the community-based coral reefs.